STUDI DESKRIPTIF WORKPLACE DEVIANT BEHAVIOR (Studi Pada Karyawan Bagian Produksi Di Pabrik Kelapa Sawit (PKS) Sei Pagar PT Perkebunan Nusantara V (Persero)) - Andri Aprinanda (SISI LAIN REALITA, 2020)
Sei Pagar Palm Oil Mill is a state-owned company that manages palm oil processing in Riau Province. The processed product produced is CPO (crude palm oil). The unit handling this is the executive employee for the production department. From the results of the preliminary study, there are symptoms that indicate deviant behavior in the workplace. This study was conducted with the aim of answering the question of whether there is a workplace deviant behavior (WDB) among implementing employees at the Sei Fence oil palm factory. The number of participants of this research is 98 production employees. The measuring instrument used in this study is the Measure of Workplace Deviance (MWB) which was adapted from a measuring instrument developed by Bennett & Robinson (2000). The results showed that 31.7% workplace deviant behavior among employees in the production division of the Sei Fence palm oil mill was determined by Job Stress while the remaining 68.3% was influenced by other factors not examined. Another result is that there is an effect of job stress on the interpersonal deviant and there is an effect of job stress on organizational deviants.